ANALISIS KINERJA DAN PROFESIONALISME TENAGA KEPENDIDIKAN BERDASARKAN “COMPETENCY – BASED HUMAN RESOURCE (CBHR) DI UNIVERSITAS PGRI SEMARANG - Violinda, Qristin (JAB (Jurnal Akuntansi & Bisnis), 2017)
The current professionalism of education personnel is needed in order to realize the quality and quantity of good education, because professional work itself can create superior performance. Competency-Based Human Resource (CBHR) is one of the important instruments in the development of professionalism of educational personnel in order to achieve superior performance improvement and able to compete both nationally and internationally, so undoubtedly one day our education parallel with the education of other countries by not ignoring the aspect practical politics of education that requires an atmosphere and an educational policy climate. This research wishes to analyze the benefits and effects of the Competency-Based Human Resource (CBHR) program as a form of a cutting-edge management program within the national education context that enables a change to the professionalism of educational personnel. The number of samples in this study are 80 educational staffs at the University of PGRI Semarang. Determination of the sample in this study using a simple random sampling method. Data processing in this research use SPSS 21 analysis method. Based on the result of statistical test with multicollinearity analysis, it is found that Competency-Based Human Resource (CBHR) has a significant relationship to the performance of educational staff at PGRI University Semarang but for professionalism, Competency-Based Human Resource (CBHR) does not have a significant relationship to the professionalism of education personnel at the University of PGRI Semarang.Â Key word : Performance, Profesionalism, educational staff, CBHR